Political Control Over Media In Malaysia From 1970 Till 1999 - Hajjafari, Aria (2013)
This study examines the political control over the media in Malaysia in the years 1970-1999. It seeks to understand the situation of media freedom in the country where the Internet however remains unfettered in line with upholding civil liberties and maintaining democratic spaces but censorship is a growing issue in Malaysia where was ranked 141st in the Worldwide Press Freedom Index by Reporters Without Borders and was also given a "Not Free" status on the Freedom in the World report by Freedom House. This study examines the history of media control in the country with paying closer attention to the period from Independence to 1999 which not only includes pre-colonial Malay sultanate and British colonialist era but also it contains the media situation in Malaysia after Independence which comprise the May 13th thirteenth tragedy, October 27th ―Operasi Lalang‖ 1987, Asian Financial Crisis and Reformasi Movement (1997-1999). It would appear that the issue of the control of the mass media is as old as the history of mass media in the country. The study begins with a close examination of the various laws and regulations that exist in the country and looks at the historical significance of these laws. This study explains with a detailed description of ownership of the current mainstream media who owns the largest media conglomerate in the country. The research employs a main method of data collection. This method of data collection is through in-depth interviews with Malaysian informants who are directly or indirectly related to the media in Malaysia.